Voucher Reinforcement Decreases Psychiatric Symptoms in Young People in Treatment for Drug Use Disorders – A Post Hoc Secondary Analysis of a Randomized Controlled Trial. Issue 3 (3rd July 2021) - Hesse, Morten; Thylstrup, Birgitte; Karsberg, Sidsel; Mulbjerg Pedersen, Michael; Pedersen, Mads Uffe
Abstract: Objective: This multicenter, parallel randomized, open study examined the effect of using vouchers and session reminders as an added element to outpatient treatment for drug use disorders in youth. It was hypothesized that being randomly assigned to a contingency management condition would lead to a reduction of psychiatric symptoms, and that this reduction would be mediated through abstinence and treatment completion. Methods: A total of 460 participants aged 15 to 25 years from nine outpatient sites were randomized to one of four treatment conditions (standard treatment alone [STD], i.e., 12 sessions using motivational interviewing and cognitive behavioral therapy, STD plus vouchers for attendance [VOU], STD plus text reminders [REM], or STD plus vouchers and text reminders [REM + VOU]). Participants' symptoms of psychological distress were assessed using the YouthMap 12 instrument at intake, and at 3, 6, and 9 months post-treatment initiation. Interviewers were blinded to interventions. Results: 114 participants were randomized to STD, 112 to REM, 113 to VOU, and 121 to VOU + REM. 69 clients were never interviewed for follow-up, leaving 391 for analysis ( n = 90, n = 94, n = 99, n = 108). The mean age was 20.5 years ( SD = 2.6), 23% were female, and 34% reported having a psychiatric diagnosis. Random effects regression showed that participants randomized to one of the two voucher-based conditions experienced significantly steeper declines in symptoms compared with STD ( p < .01). Structural equation modeling results indicated that the effects of contingency management on symptoms were mediated through abstinence, but not sessions attended. Conclusions: Adding contingency management to interventions for drug use disorders can reduce symptoms of psychological and emotional distress among populations of treatment-seeking youth, in part due to indirect effects through abstinence at follow-up. The data is collected from a clinical trial registered as ISRCTN27473213, at https://www.isrctn.com/ .